A solo career in Brunei Darussalam - Pambudi, Ongky Satya (Innovation in Health for Society, 2021)
Working as a nurse in another country is very interesting as many healthcare systems need to be learned. A few patients have a specific disease requiring innovative approaches to reduce adverse outcomes. In this article, we explained our experience being nurses in Brunei Darussalam. Patients transition from highly supportive medical environments filled with the possibility of a large number of physicians, nurses, aides, and other professionals to non-medical environments filled with formal and informal carer support that is frequently supplemented by visits from home care nurses when they leave the hospital and return home with home nursing care. Patients and carers may have difficulty making sense of the information provided to them by different clinicians before being discharged from the hospital and by home care nurses. This information can often be inconsistent. Providers, for their part, frequently have an incomplete awareness of the patient's home environment and the skills of both the patient and the carer. Despite these challenges, patients are most expected to care for themselves and be actively involved in their treatment to the extent necessary to own and control their medical problems. Keywords: Healthcare; innovation in health; caring for the human being; chronic care; nursing career